Potentials for Promoting Oil Products Identified from Traditional Knowledge of Native Trees in Burkina Faso - Ouédraogo, Amadé; Lykke, Anne Mette; Lankoandé, Benjamin; Korbéogo, Gabin (Ethnobotany Research and Applications, 2013)
Oil products from native trees are far from fully exploited in West Africa. Only well-known species like shea (Vitellaria paradoxa C.F. Gaertn.) and oil palm (Elaeis guineensis Jacq.) receive attention. We used quantitative questionnaires in 12 villages in Western Burkina Faso to assess the knowledge of four ethnic groups on 28 tree species and how their oil is used. Sixteen species were used the most. Among them, V. paradoxa, E. guineensis, Carapa procera DC., Pentadesma butyracea Sabine and Lophira lanceolata Tiegh. ex Keay received the most citations. Oils were used for soap (22%), food (21%), medicine (19%), body care (18%) and hair care (14%). Significant differences were found among ethnic groups concerning knowledge and preferences of oil products. Apart from the well-known species, C. procera, L. lanceolata and P. butyracea appear to be promising species for promotable oil products and a number of less known species may show potentials as well. <!–[endif] –>